Bench-to-bedside review: Chest wall elastance in acute lung injury/acute respiratory distress syndrome patients - Gattinoni, Luciano (BioMed Central, 2004)
The importance of chest wall elastance in characterizing acute lung injury/acute respiratory distress syndrome patients and in setting mechanical ventilation is increasingly recognized. Nearly 30% of patients admitted to a general intensive care unit have an abnormal high intra-abdominal pressure (due to ascites, bowel edema, ileus), which leads to an increase in the chest wall elastance. At a given applied airway pressure, the pleural pressure increases according to (in the static condition) the equation: pleural pressure = airway pressure × (chest wall elastance/total respiratory system elastance). Consequently, for a given applied pressure, the increase in pleural pressure implies a decrease in transpulmonary pressure (airway pressure – pleural pressure), which is the distending force of the lung, implies a decrease of the strain and of ventilator-induced lung injury, implies the need to use a higher airway pressure during the recruitment maneuvers to reach a sufficient transpulmonary opening pressure, implies hemodynamic risk due to the reductions in venous return and heart size, and implies a possible increase of lung edema, partially due to the reduced edema clearance. It is always important in the most critically ill patients to assess the intra-abdominal pressure and the chest wall elastance.